The Role of Innovation and Digitalisation in Enhancing the Competitiveness of SMEs in the Digital Economy Era - Redo, Redo; Panji , Sarinopalita Handayani; Yulyani, Yulyani; Suwarni, Suwarni; Anzori, Anzori (Journal of Management, Economic, and Accounting, 2026)
MSMEs play a strategic role in supporting national economic growth and job creation. However, amidst the digital economic transformation, MSMEs face significant challenges in maintaining competitiveness due to limited innovation and low technology adoption. This conceptual article aims to analyze the role of innovation and digitalization in enhancing MSME competitiveness in the digital economy era.Through a literature review and theoretical approaches such as the Resource-Based View (RBV), Entrepreneurial Orientation (EO), and the Technology Acceptance Model (TAM), this article explains that product, process, and marketing innovation supported by digital transformation are key factors in enhancing MSME competitive advantage. The integration of innovation and digitalization enables MSMEs to expand markets, improve operational efficiency, and build sustainable added value.This article also provides managerial implications for MSMEs and policymakers in strengthening innovation- and technology-based entrepreneurial strategies.